2011
DOI: 10.1099/jmm.0.032482-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extended-spectrum β-lactamase-producing Escherichia coli and Klebsiella pneumoniae isolates from the community in Morocco

Abstract: Of 803 community Escherichia coli (n5767) and Klebsiella pneumoniae (n536) isolates collected from patients with urinary tract infections in three Moroccan cities, 10 E. coli (1.3%) and 2 K. pneumoniae (5.6 %) isolates were shown to produce extended-spectrum b-lactamases (ESBLs). PFGE revealed that the E. coli isolates comprised seven distinct genotypes. The presence of plasmids in the 12 isolates was revealed by conjugation experiments of plasmids from these Enterobacteriaceae strains with E. coli K 12 J 5 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
79
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 46 publications
11
79
1
1
Order By: Relevance
“…CTX-M may be increased due to wide use of third generation cephalosporins, especially ceftriaxone and cefotaxime or may be associated with high mobilization of the encoding genes [26]. Barlow et al [27] reported that the bla CTX-M genes have been mobilized to plasmid almost 10 times more frequently than other class A b-lactamases.…”
Section: Discussionmentioning
confidence: 99%
“…CTX-M may be increased due to wide use of third generation cephalosporins, especially ceftriaxone and cefotaxime or may be associated with high mobilization of the encoding genes [26]. Barlow et al [27] reported that the bla CTX-M genes have been mobilized to plasmid almost 10 times more frequently than other class A b-lactamases.…”
Section: Discussionmentioning
confidence: 99%
“…Other newly emerged β-lactamase enzymes are CTX-M, PER, VEB and GES [1,2]. So far about 400 different types of ESBL's have been recognized around the world [3]. They belong to Ambler molecular class A and Bush-Jacoby functional group 2be [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, the rate of resistance to third generation cephalosporins amongst ESBL producing K. pneumoniae was between (55%, ceftriaxone), to (67.4%, cefexime) (26). Although these enzymes are not effective on carbapenems, since the cephalosporin resistance results in the use of carbapenem in the treatment of infections, these isolates might be exposed to carbapenem and became resistance (27).…”
Section: Discussionmentioning
confidence: 99%
“…A polish study revealed that Most of the ESBL-producing isolates (75.7 %) had a bla CTX-M gene (29). Some studies have indicated that CTX-M-producing E. coli and K. pneumoniae have been imported from community acquired urinary tract infections into the hospital setting (27).…”
Section: Discussionmentioning
confidence: 99%